The British Colonial Legacy: Trade and Business in Bangalore (1800–1947) - Bhagyajyothi S. Kannur (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
This article explores how, during the early 19th and mid-20th centuries, British colonial government changed trade and business in Bangalore (then part of Mysore State) through administrative reforms, infrastructure development, and legal and tax systems. It examines the ways in which colonial policies influenced regional trade networks, land and labor relations, merchant classes, and urban marketplaces. The study, which draws on secondary and archival sources, contends that although colonial rule brought modernizing institutions (banking, railroads, and municipal regulations) that promoted integration and growth, these same institutions also strengthened access disparities and ingrained extractive dependency patterns. Bangalore’s economic geography is still shaped by the effects of colonial land control, trade regulation, and infrastructure design.